TÜRKİYE’DE İNSAN KRİPTOKOKKOZUNUN EPİDEMİYOLOJİSİ (1953-2003) - KANTARCIOĞLU, A. Serda; YÜCEL, Ayhan (Cerrahpaşa Medical Journal, 2014)
Background.- We carried on a systematic literature review concerning on (i) studies examining the presence of Cryptococcus neoformans in natural sources and (ii) cases of cryptococcosis reported in this country between 1953-2003 to define the epidemiological characteristics of C. neoformans and cryptococcosis in Turkey. The isolation rate of C. neoformans from natural sources in Turkey varies between 1.0% and 35.0%, however this data may not reflect frequency due to the differences of methodologies e.g. sampling, media and techniques used and the developments of the available knowledge of its ecology. In a recent large scale study covering 54 of 80 provinces of the country, 28 C.neoformans var. neoformans strain was isolated and among them 26 different karyotypes was found by PFGE, indicating a certain clonal population was not dominated in Turkey. A systematical analysis of twenty cases of cryptococcosis reported in Turkey between 1953 and 2003 was performed. For cases of cryptococcosis, overall, the majority of patients presented with CNS infections (73.2%, 30/41) and masculine predominance (63.2%, 24/38) and respectively high mortality (43.9%, 18/41) was evident in all patients.